Impacts of International Baccalaureate programmes on teaching and learning: A review of the literature. (December 2018) - Dickson, Anisah; Perry, Laura B.; Ledger, Susan
International Baccalaureate (IB) programmes are growing rapidly worldwide, driven in part by their global reputation and concept-driven, inquiry-based approach to teaching and learning. This thematic review of a range of literature sources examines the impact of IB programmes on teaching and learning, highlighting trends, challenges, and benefits. Findings of the review revealed that most of the studies, both qualitative and quantitative, examined stakeholders' perspectives or self-reported experiences of IB programmes; a very small number used research designs that control for confounding factors or allow causal inferences to be drawn. A wide range of stakeholders report that IB programmes develop research and critical thinking skills, intercultural appreciation and global awareness, as well as cultivate collaborative working cultures and creative pedagogical practices among teachers. Challenges include extra demands on teachers for lesson planning and assessment, additional stress for teachers and students, and competing demands and expectations with national requirements. Recommendations are provided which may guide future research endeavours.